Beautification of Barangay 402 Zone 41: An action research on improving the local community - Nieveras, Teddy R. (Animo Repository, 2018)
This paper showcases the improvement of the beautification of Barangay 402 Zone 41, in Sampaloc, Manila. As collaboratively framed with two of the barangay officials, the issue that was addressed is the further development of beautification of our barangay, as expressed in the clean and green programs. Utilizing the action research (AR) methodology by Coghlan and Brannick (2014), I used different tools under the first, second, and third-person skills to guide in critically analyzing and reflecting on perspectives and other data involved. Verifying my personal views and observations, my collaborators confirmed that the routine painting of the barangays street walls and gutters has been their answer to the greening of our barangay, due to space availability. With this, we came up with our barangays very first greening initiative for our first cycle. In order to holistically cover clean and green, our second cycle touched on the waste management efforts of the community by initiating and piloting a recycling activity. To make sense of the cycles in this AR, I utilized Lewins Unfreeze-Change-Refreeze Change Management Model, as well as the concept of Locality Development and the Inter-American Foundations (1994) Grassroots Development Framework (GDF). With the learnings from this AR, I was able to expand the GDF to show that change in the community does not necessarily start with the top level, but it should be a collaborative meeting between those at the top (officials) and those at the bottom (residents). This concept, as well as activities in this AR, can be used by other barangays in Manila in improving the beautification in their community, specifically on the clean and green programs.